Paradoxical tuberculosis‐associated immune reconstitution inflammatory syndrome in children. Issue 2 (14th June 2015) - Van Rie, Annelies; Sawry, Shobna; Link‐Gelles, Ruth; Madhi, Shabir; Fairlie, Lee; Verwey, Charl; Mahomed, Nasreen; Murdoch, David; Moultrie, Harry
SUMMARY: Background: Paradoxical tuberculosis (TB)‐associated Immune Reconstitution Inflammatory Syndrome (IRIS) is a common complication of combination antiretroviral treatment (cART) initiation in adults residing in resource‐limited regions. Little is known about the burden and presentation of TB‐IRIS in children initiating cART while receiving TB treatment. Methods: Prospective cohort study of South African children initiating cART while on TB treatment. Children were assessed clinically and by chest x‐ray before starting cART and at 2, 4, 6, and 12 weeks post cART initiation. All children who presented with any signs or symptoms suggestive of paradoxical TB‐IRIS were classified according to the consensus adult TB‐IRIS case definition developed by the International Network for Study of HIV‐associated IRIS (INSHI) and reviewed by an independent expert panel. Results: In 7 of the 104 children enrolled in the cohort, symptoms and/or clinical or radiological signs suggestive of paradoxical TB‐IRIS developed after a median of 14 days of cART. In two of these cases, there was agreement between the INSHI case definition and the expert panel. In an additional 3 cases, the INSHI criteria were fulfilled but the expert panel made an alternative diagnosis of pneumonia (n = 2) and poor adherence to cART (n = 1). Conclusions: The burden of paradoxical TB‐IRIS in children with underlying TB initiating cART is low. Including response to antibiotic treatment for pneumonia as a criterion for an alternative diagnosis may improve the specificity of the INSHI case definition.Pediatr Pulmonol. 2016;51:157–164. © 2015 Wiley Periodicals, Inc.